R (on the application of The Association of Independent Meat Suppliers) v Secretary of State for Environment, Food and Rural Affairs: [2017] EWHC 1961 (Administrative Court): High Court of Justice, England and Wales, Queen's Bench Division (Administrative Court): Fraser J: 27 July 2017. (9th December 2017) - Unknown
ABSTRACT: Religious slaughter – Non-stunned religious slaughter – Animal welfare – Welfare at the Time of Killing Regulations dealing with non-stunned religious slaughter of sheep – V-restrainer equipment used to restrain sheep being moved to be slaughtered in traditional Halal Slaughter – Regulations as drafted and interpreted by Department of Environment, Food, and Rural Affairs stopping use of V-restrainer to hold multiple sheep since slaughterman required to be ready to carry out slaughter immediately after animal placed in V-restraint – Claimant association of meat suppliers applying for judicial review – Seeking declaration that Regulations in respect of V-restrainer unlawful in so far as contrary to welfare of sheep as flock species, as natural flocking instincts meant sheep naturally wanted to follow one another onto V-restrainer – Whether Regulations unlawful – Whether claim brought out of time – Welfare at the Time of Killing Regulations SI 2015/1782, sch 3, para 6(1)(a) – Council Regulation (EC) No 1099/2009 of 24 September 2009 on the protection of animals at the time of killing